Investigation of photoluminescence of silicon rich nitrides multilayer thin films - Gan, Wei Chun (2010)
Silicon is a very important material in the electronics industry. However, due to its indirect bandgap characteristic, it is an inefficient light emitter. Intensive research had been conducted to come up with different types of silicon-based materials that are suitable for optoelectronic applications. Examples include amorphous silicon nitride (a-SiN:H) and amorphous silicon carbide (a-SiC:H). In addition, multilayer thin films consisting of various combinations of silicon-based materials have also been proposed to address this issue. Such combinations include a-SiC:H/a-Si:H multilayers [2] and a-SiNx/a-Si multilayers [3].